Islamic Jurisprudence Studies on Homosexuality, Lesbianism, and Masturbation/Masturbation - Fitri Amanda Hasibuan; Rayhan Riend Al Alfiq; Fitrah Ade Dikiansya (Jurnal Sahabat ISNU SU, 2025)
This study discusses homosexual, lesbian and masturbation issues from the perspective of Islamic jurisprudence, which are contemporary sexual issues that often cause debate in modern society. This phenomenon not only touches moral and social aspects, but also requires a comprehensive and argumentative explanation of Islamic law. In this study, the author analyzes the views of ulama from four schools of thought (Hanafi, Maliki, Syafi'i, and Hanbali) regarding these practices, based on the arguments from the Koran, Hadith, as well as the rules of ushul fiqh and maqashid sharia. Homosexuality and lesbianism are generally considered forms of sexual deviation that are forbidden in Islam, with reference to the story of the Prophet Lut as the theological and jurisprudential basis. Meanwhile, the legal status of the practice of masturbation or masturbation is debated; Some scholars prohibit it absolutely, while others allow it in emergency situations or as an effort to prevent adultery. This study uses a qualitative-descriptive approach with library research to in-depth examine Islamic texts and interpretations by classical and contemporary scholars. This study is expected to provide a more balanced and objective understanding of the limits of Islamic law in maintaining the sexual morality of Muslim individuals and provide preventive solutions to sexual deviations in the modern era. The results show that Islam emphasizes the importance of maintaining fitrah (natural disposition) and personal purity as part of the objectives of law (maqasid sharia).